165 Applicability of duke activity scale index (DASI) in perioperative prediction of postoperative complications for gynaeoncology patients. (13th November 2020) - Sevinyan, L; Tailor, A; Williams, P; Prabhu, P; Madhuri, K
Abstract : Introduction: Due to increasing number of patients with multiple comorbidities requiring gynaeoncological interventions there is an unmet need for an accurate perioperative risk prediction stratification. DASI is a 12 item self-reported questionnaire based around commonly performed activities. DASI determines functional capacity through conversion to Metabolic Equivalent of Tasks (METs), which have been shown to indicate fitness for surgery. In our study we explore the accuracy of DASI in prediction of postoperative outcomes in the context of gynaeoncology. Methods: A retrospective data for 141 patients was collected using a dedicated database or patients' notes at a tertiary oncology centre. All of the patients had filled DASI questionnaire prior to surgery, which we used for the analysis. Actual postoperative complications which occurred within 30 days of the surgery were also recorded. DASI score was then compared with the occurrence of postoperative complications. Results: N=141. DASI has not found to be a statistically significant model for prediction of postoperative complications in the general population of the gynaeoncology patients (AUC-0.433). However we were able to show that a 25 point higher DASI score is predicted to deliver 1 day less in hospital. We also found that DASI score could be promising for patients with ovarian and cervical malignancy (AUC-0.634 and AUC 0.750 respectively), but there were not enough patients to validate the findings. Conclusions: DASI could be useful in perioperative estimation of postoperative complications for ovarian and cervical cancer patients. A study with a larger sample size and multi-centre prospective study are currently underway to validate the findings.